Dream analysis in relation to Prakrithi and diseases: A study at National Ayurveda Teaching Hospital, Borella: De Silva R.H.S.K.1*, Pathirana L.2 and Dharmathunga K.G.S.P.1 (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2024)
This study explores the relationship between dreams, individual constitution (Prakrithi), and disease manifestation within the Ayurvedic framework. Dreams were examined as potential diagnostic tools in Ayurveda, with a focus on understanding how dream content correlates with Prakrithi and disease types. Therefore, this study was conducted over six months at the National Ayurveda Teaching Hospital, with 210 volunteer participants selected using a stratified sampling method. Data were collected through selfquestionnaire forms and analyzed using a mixedmethod approach, combining qualitative and quantitative techniques. Demographic analysis revealed a predominantly female sample, with the highest frequency observed in the 18-27 age group. Pitta-Kapha prakrithi was most prevalent among participants, with Pitta dosha being the predominant dosha. Most participants reported infrequent dreaming, with a minority experiencing dreams close to waking up. Nearly half of the participants reported dreaming while suffering from a disease, predominantly respiratory system-related diseases. The study did not find a significant correlation between dream frequency, disease type, and Prakrithi. However, it acknowledges the influence of factors such as life satisfaction, attitudes, and emotions on dream patterns and health outcomes. Further research is needed to explore the complex interplay between individual constitution, dream content, and disease manifestation within Ayurveda. While this study provides valuable insights into the role of dreams in Ayurvedic diagnosis and treatment, additional research is necessary to deepen understanding in this area. By considering broader factors beyond Ayurvedic principles, future studies can elucidate the comprehend relationship between dreams, health, and individual constitution.